A Parceria público privada na Universidade Federal Rural da Amazônia - MOTA, Ricelli Cristiana dos Santos (Universidade Federal do Pará, 2025)
This production aims to study Public Private Partnerships (PPPs), at the Federal Rural University of the Amazon. PPPs are an alternative that will contribute to universities carrying out their mission in the current context, taking into account their advantages for the public sector, in this case in particular, in public universities. The aim is to propose how these PPPs can be established, bringing a legal aspect, with benefits for both the institution and the Company involved, mainly, satisfaction with the services provided to the target audience: students, teachers, technicians and the community at large. In this context, the general objective is to analyze the PPPs celebrated with a Federal Education Institution (IFES) that contributes to its final institutional development; and as specific: verify the documents that deal with the practice of public-private partnerships at UFRA, through contracts and PPPs carried out with the support foundation (FUNPEA); analyze the PPPs signed between Ufra and supporting foundations (FADESP and FUNPEA); analyze the perception of managers from the UFRA Contracts and Agreements Department; prepare a Normative Instruction that facilitates the establishment of PPPs at UFRA. This research contributes to the importance of investigating the way in which PPPs are applied and developed more efficiently at UFRA, as well as the main challenges to leveraging culture within UFRA, seeking ways to increase the number of PPPs signed at the institution. , aiming for benefits for both companies, the University and society. Documentary and field research will be used as a methodology, with analysis of reports and interviews with employees working in the UFRA Contracts and Agreements Directorate. The conclusions highlight the significant role of PPPs in several key aspects for institutional growth and improvement, such as investments in construction, renovation and modernization of the institution's physical facilities, directly benefiting the learning environment and promoting an infrastructure suited to the needs of students.